Fabrication and characterization of two-terminal graphene resistive memories - Yi, Xiang (2014)
In the recent years, graphene-based atomic switches joined the non-volatile memory race. Many teams reported graphene-based or graphite-based switches atomic switches. The breakdown phenomenon of graphene nano-ribbons or graphene sheets were also studied by many groups to analyse the carbon-based interconnects and current-induced reliability limit by evaluating the current density sheet resistance or other parameters. This project successfully fabricated two-terminal nano-graphene devices with commercial CVD graphene samples. By studying these devices, the project demonstrated the application of graphene as resistive memories. Our team found that the breakdown of graphene could be achieved under both vacuum and atmospheric pressure, and the breakdown voltage is higher under vacuum than in air, which may be caused by the absence of O2. Different from the breakdown process, the repair of graphene could only be achieved under vacuum for our CVD graphene switches, and one hypothesis is that the carbon atoms chains that formed under a strong electrical field could react with O2 such that it disappears before the two sides of broken graphene could be reconnected. Besides, multi-stage breakdown and repair were observed with graphene sheet. Those devices displayed good robustness, and the team successfully switched the graphene device for 1000 cycles with an average OFF to ON state resistance ratio of 472.